A comparative review of CET4 essay writing assessments insights from the CEFR level descriptors and CET4 writing rubrics - Li, Changlin; Nik Aloesnita, Nik Mohd Alwi; Mohammad Musab, Azmat Ali (AJELP, 2025)
The alignment of assessment frameworks such as the Common European Framework of Reference for Languages (CEFR) and the College English Test Band 4 (CET4) has gained significant attention in language testing and assessment research. This study explores the intersections between CET4 writing rubrics and CEFR level descriptors, focusing on their implications for essay writing evaluation. Grounded in Robinson’s (2001) Cognition Hypothesis (CH) and Skehan’s (1998) Limited Attentional Capacity Model (LACM), this research examines the role of task complexity in influencing lexical and syntactic outcomes in writing performance. Robinson’s CH posits increased task complexity enhances linguistic output, encouraging richer lexical and syntactic performance. In contrast, Skehan’s LACM highlights the trade-offs in accuracy, fluency, and complexity under cognitive constraints. Recent studies have applied these frameworks to investigate task complexity dimensions, such as “+/- planning time (PT)” and “+/- few elements (FE),” in standardized tests like CET4. Empirical findings from the past five years indicate significant correlations between task complexity, lexical diversity, and CEFR-aligned performance measures (Bui & Skehan, 2018a; Lambert et al., 2017; Xu & Zhang, 2023). Moreover, this study reviews research on aligning CET4 writing rubrics with CEFR descriptors to identify overlapping and divergent assessment criteria. Findings suggest that incorporating CEFR descriptors enhances the validity and fairness of CET4 assessments, bridging local and global standards in language evaluation. By synthesizing theoretical insights and recent empirical evidence, this study offers a nuanced understanding of writing assessment practices, informing educators and policymakers about the potential for harmonizing these frameworks.